(untitled) (Third Sector Social Economic Review, 2020)
The problem caused by the new type of coronavirus, Covid-19, which has turned into a global pandemic, continues at full speed. Although social (physical) distance practices, which are accepted as the only valid measure until vaccination studies are successful, reduce the rate of spread of the pandemic, it is thought that countries will not be able to continue their effectiveness due to the inability to determine a common strategy. The increase in economic costs caused by the pandemic and the fact that it does not disappear completely negatively affects the decisions of governments regarding social distance practices. This study examines the effect of the social (physical) distance policies of 13 selected countries, where the pandemic reached serious dimensions, on the number of cases with the Panel Quantile Regression Analysis. The countries in question were divided into two different groups as weak and strongly responsive countries according to the Stringency Index scores, and it was identified that the countries that reacted strongly in the first 10 weeks of the pandemic were more successful according to the Stringency Index Scores. Therefore, these days when the second wave of the pandemic is being discussed, it is seen as an important issue that all countries take a similar action towards social distance practices. In the face of the global pandemic, no government will be able to solve the problem with its initiative and all countries should determine a common strategy.